2017
DOI: 10.1111/jcpp.12769
|View full text |Cite
|
Sign up to set email alerts
|

Implicit identification with death predicts change in suicide ideation during psychiatric treatment in adolescents

Abstract: Background Suicidal thoughts and behaviors are major public health concerns in youth. Unfortunately, knowledge of reliable predictors of suicide risk in adolescents is limited. Promising research using a death stimuli version of the Implicit Association Test (Death IAT) indicates that stronger identification with death differs between adults with and without a history of suicidal thoughts and behaviors and uniquely predicts suicide ideation and behavior. However, research in adolescents is lacking and existing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
51
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(65 citation statements)
references
References 42 publications
10
51
2
Order By: Relevance
“…In contrast to other studies of adolescents with psychiatric disorders in which IAT d-scores were strongly correlated with self-report measures of SI (Harrison et al ., 2014 ; Glenn et al ., 2017 ), in the present study these two measures were not significantly associated. Our sample of adolescents, however, is notably younger than the participants who have been studied in prior investigations of the IAT (Nock et al ., 2010 ; Harrison et al ., 2014 ; Barnes et al ., 2016 ; Glenn et al ., 2017 ); therefore, they may not have the emotional maturity or capacity for self-reflection to accurately and explicitly report their thoughts and feelings about death and suicide (Weil et al ., 2013 ). Consistent with this view, we found that an earlier developmental stage at baseline, as assessed by self-report Tanner, was associated with larger IAT d-scores.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…In contrast to other studies of adolescents with psychiatric disorders in which IAT d-scores were strongly correlated with self-report measures of SI (Harrison et al ., 2014 ; Glenn et al ., 2017 ), in the present study these two measures were not significantly associated. Our sample of adolescents, however, is notably younger than the participants who have been studied in prior investigations of the IAT (Nock et al ., 2010 ; Harrison et al ., 2014 ; Barnes et al ., 2016 ; Glenn et al ., 2017 ); therefore, they may not have the emotional maturity or capacity for self-reflection to accurately and explicitly report their thoughts and feelings about death and suicide (Weil et al ., 2013 ). Consistent with this view, we found that an earlier developmental stage at baseline, as assessed by self-report Tanner, was associated with larger IAT d-scores.…”
Section: Discussioncontrasting
confidence: 72%
“…To address these limitations, researchers examining risk for suicidal behaviors have begun to use cognitive tasks involving implicit measurements that do not rely on self-report (Cha et al ., 2010 ; Barnes et al ., 2016 ; Harrison et al ., 2018 ). One such task is a version of the Implicit Association Test (IAT) that measures response latencies to speeded judgments of pairs of death-related and self-related words (Nock et al ., 2010 ; Glenn et al ., 2017 ). Several studies have shown that individuals with a history of suicide attempts exhibit pronounced implicit self-identification with death/suicide (Nock et al ., 2010 ; Barnes et al ., 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nock & Banaji, 2007), nonclinical samples (Glenn, Kleiman, Cha, Nock, & Prinstein, 2016;Glenn, Werntz et al, 2017), different versions of the IAT (Glenn et al, 2016;Nock & Banaji, 2007), and different statistical analyses (Randall, Rowe, Dong, Nock, & Colman, 2013). Some studies found results consistent with the original findings (i.e., mean differences in the S-IAT between clinical and nonclinical groups), while others did not (Barnes et al, 2017;Glenn, Kleiman et al, 2017;Glenn, Werntz, et al, 2017). As far as we know, apart from these conceptual replications, there has been no direct replication of Nock et al's (2010) study.…”
Section: Suicide-implicit Association Testmentioning
confidence: 87%
“…One study found that d/s IAT ratings were predictive of future suicide attempts in adults who had presented for suicide risk in the emergency department (Nock et al., ). Another study found that d/s IAT scores at psychiatric admission for adolescents predicted their suicide ideation severity at discharge, especially for adolescents who had longer stays (Glenn et al., ). The current study incorporated the d/s IAT as an additional measure of current suicide risk.…”
mentioning
confidence: 99%